Review of Multi-material Additive Manufacturing - Tan, J. L. (2016)
Recently, Additive Manufacturing (AM) has seen a surge in interest with companies using the technology for prototyping andfunctional parts. It offers certain advantages over its traditional manufacturing counterpart. However, AM’s capabilities can be further enhanced by incorporating multiple materials in its processes. This paper presents the progress on the advances in multiple materials in different AM methods.